Nitrate Esters Chemistry and Technology - Liu, Jiping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The idea of this book is to present the up-to-date research results on Nitrate Esters as explosive materials. It covers many aspects including the material structures, nitrating agent, chemical synthesis devices, preparation technology, and applications etc. In particular, this work sheds light on the comprehensive utilization and thorough destruction of the used Nitrate Easters which is crucial for preventing repeated pollution. This is a highly informative and instructive book providing insight for the researchers working on nitrating theory, energetic materials and chemical equipments.
Introduction of Nitrate Esters -- Characteristics of Nitrating Agents -- Equipment and Process of Nitration Reactions -- Mononitrate Esters -- Dinitrate Esters -- Nitroglycerine -- PentaerythritolTetranitrate -- Other Polynitrate Esters -- Azidonitrate Esters -- Cellulose Nitrate Esters -- Starch Nitrate Esters -- Sugar Nitrate Esters -- Disposal and Comprehensive Utilization of Waste Nitrate Esters.
Keywords: Chemistry, Technical; Continuum mechanics; Thermodynamics; Engineering geology; Refuse and refuse disposal; Industrial Chemistry; Continuum Mechanics; Thermodynamics; Geoengineering; Waste Management/Waste Technology